How Critical Thinking Can Be Cultivated in Middle School Students - Ibrohimova Muxtasarxon Masumxon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Critical thinking is a foundational skill for 21st-century learners, enabling them to analyze information, solve problems, and make thoughtful decisions. Middle school is a crucial period for developing such skills, as students begin transitioning from concrete to abstract thinking. This paper explores effective strategies for cultivating critical thinking among middle school students through inquiry-based learning, problem solving tasks, and reflective discussions. It also examines the role of teacher guidance, classroom environment, and curriculum design in fostering analytical reasoning. The study emphasizes the importance of integrating critical thinking into everyday learning to equip students with skills that extend beyond academic success.